Answer:
[tex]x=\frac{27}{10}[/tex]
Step-by-step explanation:
Assuming that the beginning equation is [tex]\frac{x}{2} -\frac{1}{5} =\frac{x}{3} +\frac{1}{4}[/tex]
First, we should find the common denominator of each of fractions. For all of these denominators, 60 is the smallest common denominator
[tex]\frac{x}{2}(\frac{30}{30}) -\frac{1}{5}(\frac{12}{12}) =\frac{x}{3}(\frac{20}{20}) +\frac{1}{4} (\frac{15}{15}) \\\\\frac{30x}{60}-\frac{12}{60} =\frac{20x}{60}+\frac{15}{60}[/tex]
Now, we can multiply each side by 60, which will remove the fractions
[tex]30x-12=20x+15[/tex]
Now we can add 12 to each side
[tex]30x=20x+27[/tex]
Now subtract 20x from each side
[tex]10x=27[/tex]
And lastly, divide each side by 10
[tex]x=\frac{27}{10}[/tex]